Applications of Nanovaccines for Disease Prevention in Cattle - Maina, Teresia W.; Grego, Elizabeth A.; Boggiatto, Paola M.; Sacco, Randy E.; Narasimhan, Balaji; McGill, Jodi L. (Frontiers in Bioengineering and Biotechnology, 2020)
Vaccines are one of the most important tools available to prevent and reduce the incidence of infectious diseases in cattle. Despite their availability and widespread use to combat many important pathogens impacting cattle, several of these products demonstrate variable efficacy and safety in the field, require multiple doses, or are unstable under field conditions. Recently, nanoparticle-based vaccine platforms (nanovaccines) have emerged as promising alternatives to more traditional vaccine platforms. In particular, polymer-based nanovaccines provide sustained release of antigen payloads, stabilize such payloads, and induce enhanced antibod- and cell-mediated immune responses, both systemically and locally. To improve vaccine administrative strategies and efficacy, they can be formulated to contain multiple antigenic payloads and have the ability to protect fragile proteins from degradation. Nanovaccines are also stable at room temperature, minimizing the need for cold chain storage. Nanoparticle platforms can be synthesized for targeted delivery through intranasal, aerosol, or oral administration to induce desired mucosal immunity. In recent years, several nanovaccine platforms have emerged, based on biodegradable and biocompatible polymers, liposomes, and virus-like particles. While most nanovaccine candidates have not yet advanced beyond testing in rodent models, a growing number have shown promise for use against cattle infectious diseases. This review will highlight recent advancements in polymeric nanovaccine development and the mechanisms by which nanovaccines may interact with the bovine immune system. We will also discuss the positive implications of nanovaccines use for combating several important viral and bacterial disease syndromes and consider important future directions for nanovaccine development in beef and dairy cattle.